2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037091
|View full text |Cite
|
Sign up to set email alerts
|

An electrical impedance tomography (EIT) multi-electrode needle-probe device for local assessment of heterogeneous tissue impeditivity

Abstract: Electrical Impedance Tomography (EIT) is an image reconstruction technique applied in medicine for the electrical imaging of living tissues. In literature there is the evidence that a large resistivity variation related to the differences of the human tissues exists. As a result of this interest for the electrical characterization of the biological samples, recently the attention is also focused on the identification and characterization of the human tissue, by studying the homogeneity of its structure. An 8 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…There are many publications on the development of electric impedance tomography devices [3][4][5][6][7][8][9][10]. Paper [3] addresses the development of a low-cost implementation of the non-disruptive control system based on the EIT.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many publications on the development of electric impedance tomography devices [3][4][5][6][7][8][9][10]. Paper [3] addresses the development of a low-cost implementation of the non-disruptive control system based on the EIT.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The device is based on the Arduino UNO board and the EIT board, which combines a probe signal generator and switches. Paper [4] tackles the development of an electrode system for the EIT and contains a description of the portable EIT system. Paper [5] includes a description of a data collection and transmission device based on the Arduino 2560 board with external switches and measurement of potentials relative to the common point.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Several research groups [6,17] reported the finite element simulation of the electric fields surrounding the needle tip in different tissue models. The electrical impedance tomography using a multi-electrode array is expected to provide the lateral and spatial information of the needle [27,28]. Finally, the feasibility of the intra-articular injection therapy based on the impedance monitoring with the monopolar injection needle and the algorithm to detect the target tissue will be tested in an animal model and clinical trials.…”
Section: Impedance Monitoring Of the Needle Positioningmentioning
confidence: 99%
“…Although this approach is often sufficient in obtaining general information regarding the tissue it may not be able to discriminate between tissue conductivity deep underneath the surface. Tissue variations can exist well below the skin surface and electrodes may not able to detect this change in conductivity (Meroni et al, 2017 ). This is especially the case for prostate cancer (Meir and Rubinsky, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The physical distance and the neighboring organs can all attribute to noise in surface electrode measurements. In contrast, research has been conducted into utilizing internal electrodes that are placed within the object of interest, much like needles, in order to perform the imaging procedure (Halter et al, 2011 ; Mishra et al, 2011 , 2013 ; Wan et al, 2013 ; Fukushima et al, 2015 ; Meir and Rubinsky, 2015 ; Meroni et al, 2017 ; Kwon et al, 2018 ; Park et al, 2018 ; Abbasi et al, 2020 ). With the use of needle probes, the voltage measurements can be taken deep underneath the skin surface to the exact depth of the suspicious tissue under inspection.…”
Section: Introductionmentioning
confidence: 99%